Combining Cocatalyst and Oxygen Vacancy to Synergistically Improve Fe2O3 Photoelectrochemical Water Oxidation Performance - Chen Liu; Jiajuan Li; Wenyao Zhang; Changqing Zhu (Crystals)
Considering the poor conductivity of Fe2O3 and the weak oxygen evolution reaction associated with it, surface hole accumulation leads to electron hole pair recombination, which inhibits the photoelectrochemical (PEC) performance of the Fe2O3 photoanode. Therefore, the key to improving the PEC water oxidation performance of the Fe2O3 photoanode is to take measures to improve the conductivity of Fe2O3 and accelerate the reaction kinetics of surface oxidation. In this work, the PEC performances of Fe2O3 photoanodes are synergistically improved by combining loaded an FeOOH cocatalyst and oxygen vacancy doping. Firstly, amorphous FeOOH layers are successfully prepared on Fe2O3 nanostructures through simple photoassisted electrodepositon. Then oxygen vacancies are introduced into FeOOH-Fe2O3 through plasma vacuum treatment, which reduces the content of Fe-O (OL) and Fe-OH (-OH), jointly promoting the generation of oxygen vacancies. Oxygen vacancy can increase the concentration of most carriers in Fe2O3 and form photo-induced charge traps, promoting the separation of electron holes and enhancing the conductivity of Fe2O3. The other parts of -OH act as oxygen evolution catalysts to reduce the reaction obstacle of water oxidation and promote the transfer of holes to the electrode/electrolyte interface. The performance of FeOOH-Fe2O3 after plasma vacuum treatment has been greatly improved, and the photocurrent density is about 1.9 times higher than that of the Fe2O3 photoanode. The improvement in the water oxidation performance of PEC is considered to be the synergistic effect of the cocatalyst and oxygen vacancy. All outstanding PEC response characteristics show that the modification of the cocatalyst and oxygen vacancy doping represent a favorable strategy for synergistically improving Fe2O3 photoanode performance.